Local Anaesthetic Effectivity and Toxicity of Fomocaine, Five N-free Fomocaine Metabolites and Two Chiralic Fomocaine Derivatives in Rats Compared with Procaine - Fleck, Christian; Kämena, Matthias; Tschritter, Lars; Kersten, Lothar; Seeling, Andreas; Glassl, Peter; Oelschläger, Herbert (Arzneimittelforschung, 2001)
Until now, no optimal local anaesthetic drug with long lasting effect and low toxicity has been developed. Fomocaine (CAS 17692-39-6), introduced in the German extrapharmacopoeia (DAC) in 1979, is a local anaesthetic, which is largely in accordance with these aspects. Now the basic ether fomocaine, its metabolites O/ Se 9 (CAS 3006-96-0), O/Se 10 (CAS 31719-76-3), O/Se 11, O/Se 12 (CAS 64264-21-7) and M5 and its chiralic derivatives O/G 3 and O/G 5 were compared with procaine (CAS 59-46-1) and characterised more in detail in rats. The metabolism of fomocaine was investigated earlier with 14C-fomocaine in rats and beagle dogs. Rac-O/G 3 and Rac-O/G 5 could be separated into the enantiomers via the di-astereomeric salts. Basing on standard methods for the testing of the local anaesthetic effects (estimation of infiltration and conduction anaesthesia in rat tail, measurement of corneal anaesthesia) and using a couple of tests characterising the side effects and toxicity of local anaesthetic (paresis of the N. ischiadicus, tissue irritation, determination of the approximative i.p. LD50) it can be concluded that:a) The very good surface anaesthesia caused by fomocaine could be stated, but, as expected, concerning conduction anaesthesia, procaine is better qualified for clinical use.b) Fomocaine is much more effective in conduction and surface anaesthesia than its chiralic derivatives O/G 3 and O/ G 5.c) Differences between the two enantiomers of the O/G-substances have been found, but these little discrepancies are without practical relevance. In the case of O/G 5, agonistic effects of both enantiomers could be shown.d) Fomocaine undergoes extensive biotransformation with subsequent formation of 14 metabolites. Five of them (O/Se 9-O/Se 12; M5) are N-free and do not show any pharmacological activity.e) Compared to other local anaesthetics, fomocaine is relatively non-toxic (nearly no tissue irritation, high approximative LD50), however, surprisingly the toxicity of the reference substance procaine has been found to be lower after i.p. administration instead of i.v. administration in comparison with fomocaine.
Keywords: Anaesthetics, local; CAS 59-46-1; CAS 17692-39-6; Fomocaine, chiralic derivatives, local anaesthetic effectivity, metabolites, rat, toxicity; Procaine, local anaesthetic effectivity, rat, toxicity